Antecedents and Consequences of State Civil Apparatus Performance at the Paser Regency Regional Secretariat - Widiasie, Lynie; Amir Fikri; Geraldina, Ira (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the factors that influence the performance of the State Civil Apparatus at the Regional Secretariat of Paser Regency. The type of research used is quantitative research. Data collection technique used is to use a questionnaire. The population in this study were all State Civil Apparatuses within the Regional Secretariat of Paser Regency, namely 168 people. The sampling technique used was Simple Random Sampling and succeeded in determining a total of 63 samples. The data analysis used was multiple linear regression data analysis using the Smart PLS (SEM) calculator. The results showed that discipline has a significant effect on performance, the path coefficient value is 0.884 and the P value is 0.000 (<0.05), incentives have a significant effect on discipline, the path coefficient value is -0.173 and the P value is 0.297 (> 0.05), the work environment has a significant effect on discipline, the path coefficient value is -0.168 and the P value is 0.401 (> 0.05), motivation has a significant effect on discipline performance, the path coefficient value is 0.024 and the P value is 0.706 (> 0.05), work stress has a significant effect on motivation, the path coefficient value is 0.101 and the P value is 0.612 (> 0.05), organizational culture has a significant effect on motivation, the path coefficient results are 0.509 and the P value is 0.000 (<0.05) and leadership style has a significant effect on motivation, with a path coefficient result of 0.148 and the P value is 0.380 (> 0.05). Therefore, it is hoped that the leadership of the Paser Regency Regional Secretariat will pay attention to various determinants of employee performance